Reasons And Ways of Computer Slang and Jargon Formations - Shamieva Nargiza Abdusattarovna (Zien Journals, 2022)
This article is analyzed that computer jargon is considered as an independent (but not isolated) lexical sub-language subsystem, as a special social dialect. The lexico-semantic relations within the jargon and the ways of its word production are analyzed, taking into account active general language processes. The vocabulary of the so-called "professional" part of computer jargon is supplemented, its thematic groups are distinguished and the features of their connotations are analyzed.
Keywords: social dialect; jargon; computer slang; lexical sub- language